Review on Stenotrophomonas maltophilia: An Emerging Multidrug- resistant Opportunistic Pathogen - Majumdar, Rikhia; Karthikeyan, Hariharan; Senthilnathan, Vaishnavi; Sugumar, Shobana (Recent Patents on Biotechnology, 2022)
Stenotrophomonas maltophilia is an opportunistic pathogen that results in nosocomial infections in immunocompromised individuals. These bacteria colonize on the surface of medical devices and therapeutic equipment like urinary catheters, endoscopes, and ventilators, causing respiratory and urinary tract infections. The low outer membrane permeability of multidrug-resistance efflux systems and the two chromosomally encoded β- lactamases present in S. maltophilia are challenging for arsenal control. The cell-associated and extracellular virulence factors in S. maltophilia are involved in colonization and biofilm formation on the host surfaces. The spread of antibiotic-resistant genes in the pathogenic S. maltophilia attributes to bacterial resistance against a wide range of antibiotics, including penicillin, quinolones, and carbapenems. So far, tetracycline derivatives, fluoroquinolones, and trimethoprim-sulfamethoxazole (TMP-SMX) are considered promising antibiotics against S. maltophilia. Due to the adaptive nature of the intrinsically resistant mechanism towards the number of antibiotics and its ability to acquire new resistance via mutation and horizontal gene transfer, it is quite tricky for medicinal contribution against S. maltophilia. The current review summarizes the literary data on pathogenicity, quorum sensing, biofilm formation, virulence factors, and antibiotic resistance of S. maltophilia.
Keywords: β-lactams